Strengthening Science Literacy Through Academic Supervision: Insights from High School Science Teachers - Iriwi Louisa S Sinon; Maisyaroh Maisyaroh; Rochmawati Rochmawati (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
Academic supervision is a systematic professional development process aimed at enhancing instructors' pedagogical and professional competencies through guidance and reflection. In the context of educational challenges in West Papua, including geographical and resource constraints, comprehending teacher attitudes poses a difficulty for supervisory tactics. This study aims to investigate the perspectives of physics teachers regarding the application of academic monitoring in public and private high schools in West Papua to strengthening scientific literacy. The employed research methodology is qualitative, utilising a case study approach. Data were gathered via comprehensive interviews with nine Physics Science educators to investigate their experiences, reactions, and anticipations regarding the academic supervision process. The study's findings indicated that teacher perceptions were significantly affected by the supervisory approach, the quality of communication between teachers and supervisors, and the pertinence of the feedback provided. Educators possess adequate comprehension of the design, execution, and evaluation of academic oversight by the principal. Favourable perceptions typically foster educators' receptiveness to transformation and enhancement of instructional methodologies. It is essential for principals to comprehend the scientific content pertinent to the subject matter taught by each educator, particularly regarding scientific literacy (scientific approach). Supervisor competencies that diverge from the relevant field of study also impede the efficacy of supervision. This study theoretically enhances the discussion on teacher perceptions in academic supervision. The findings can serve as a resource for educational stakeholders to design a more contextual and effective supervision model, particularly in regions with distinct socio-cultural and infrastructural situations like West Papua.